2013
DOI: 10.1177/1050651913513903
|View full text |Cite
|
Sign up to set email alerts
|

Communication Instruction in Landscape Architecture Courses

Abstract: Communication skills are an increasingly important component of college students’ education because these skills are in high demand from employers. This study provides a close examination of communication instruction in both a typical landscape architecture class and a modified one (i.e., with the addition of formalized communication instruction that is grounded in design), analyzing changes in students’ perceptions of their own communication abilities (self-efficacy). The study reveals that in the typical cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Researchers have investigated the impact of the studio critique on self‐efficacy or ‘belief in one's capabilities to organise and execute the courses of action required to produce given attainments’ (Bandura , 3). Studies have shown that communication competence is positively correlated with critique self‐efficacy (Gaffney ) and that self‐efficacy is in turn positively correlated with specific communication instruction (Gaffney ). These findings are supported in related design literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have investigated the impact of the studio critique on self‐efficacy or ‘belief in one's capabilities to organise and execute the courses of action required to produce given attainments’ (Bandura , 3). Studies have shown that communication competence is positively correlated with critique self‐efficacy (Gaffney ) and that self‐efficacy is in turn positively correlated with specific communication instruction (Gaffney ). These findings are supported in related design literature.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are supported in related design literature. Gaffney's () research with the restructuring of a landscape architecture curriculum to include formal communication instruction found an increase in the students’ perceptions of their own communicative abilities.…”
Section: Resultsmentioning
confidence: 99%
“…Many aspects still need to be explored and summarized in future practice [13][14][15] . The contribution is hoped to improve the teaching effectiveness of the Building Code course.…”
Section: Discussionmentioning
confidence: 99%
“…A technical communication researcher, for example, may study an artifact before it is created, or during its design phase, or after it has been designed in order to revise it and make it more usable. At the same time, the researcher may play a role outside of the design process itself and may give feedback to designers on their presentations regarding their designs (see, e.g., Galbraith, McKinney, DeNoble, & Ehrlich, 2014; Dannels, 2009; or Gaffney, 2014).
Figure 3.Lateral positions.
…”
Section: Positioning the Role Of Technical Communication In Designed mentioning
confidence: 99%